‘forms of human pow’r’: Coleridge's political poetics 1794-1802 - Lloyd, J (2019)
This thesis examines how Samuel Taylor Coleridge’s choices of poetic subject, language, and form interacted with his political ideas. The poetry which Coleridge cited, to which he alluded, and to which he responded indicates his shifting political attitudes, and his place within contemporary debates. Coleridge’s early verse responds to a Whig verse tradition, especially to Mark Akenside’s poetry. Coleridge adapts Akenside’s poetics to more radical ends. Additionally, Coleridge incorporates a sentimental poetics influenced by William Lisle Bowles into his verse in order to address the critique of the French Revolution, by Edmund Burke, that its advocates lacked connection to normal human feeling and experience. Two years later, Coleridge’s Fears in Solitude quarto can be understood as speaking to two audiences. The influence of William Cowper gave these poems the appearance of Whig political respectability and theological orthodoxy, but they also progressed in dialogue with poems by the radical lecturer John Thelwall. Coleridge directs his despairing radical contemporaries to recover liberty through religious faith. However, ‘The Rime of the Ancyent Marinere’ responds to Wordsworth’s The Borderers to question Coleridge’s earlier political assertions. While Wordsworth’s drama is a repudiation of his enthusiasm for William Godwin, ‘The Rime’ offers a sceptical appraisal of Coleridge’s previous political statements and their underlying Unitarian philosophy. From 1797 to 1802, Coleridge’s career as a poet for The Morning Post complemented his political prose for the same paper. His other poetry of the period, such as Christabel and ‘Kubla Khan’, comments on the problem of abstraction in political discourse. Coleridge suggests that political leadership is only effective if it is based on genuine metaphysical insight. Consequently, ‘Dejection: An Ode’ can be read as a political poem: no longer laying claim to such insight himself, Coleridge renounces the role of the political poet.